Standardization of questionnaires of NTN and LFR on Belarusian sample - Marozau, Alexander A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article presents the results of the standardization of the questionnaires of New Questionnaire of Tolerance for Uncertainty (NQTU, or NTN) and Personal Factors of Decisions (LFD, or LFR), intended for studying the properties of acceptance-non-acceptance of uncertainty (NTN) and personal properties that influence decision-making in the broad context of life situations (LFR). A brief overview of domestic and foreign studies of tolerance for uncertainty among leaders (managers) is given. The necessity of standardization of the research tools presented in the article is grounded. Conducting intergroup comparisons made it possible to reveal significant differences in the studied properties, due to the profile of education (the kind of professional activity), the age and gender of the subjects. The estimation of the sizes of the effects of these factors on the scores of the questionnaire scales showed that they are insignificant and the measured properties are on-specific and universal with respect to their diagnosis. The test standards obtained in the Belarusian sample will allow to correlate the results of studies conducted on different groups of subjects in the future. In addition, the standardization of the questionnaires of NTN and LFR provides an opportunity to diagnose important personal qualities for managerial activity – decision-making and tolerance to uncertainty.